BIOPOLITICAL VIOLENCE: TRACES OF WAR IN THE WORKS OF LIVANELI AND VONNEGUT THE LAST ISLAND BY ZÜLFÜ LİVANELİ AND SLAUGHTERHOUSE-FIVE BY KURT VONNEGUT - KORKMAZ, İrem Şevin and TANRITANIR, Bülent Cercis (SSD Journal, 2025)
This article explores Bioplolitic Violence very briefly in a Turkish novel The Last Island of Zülfü Livaneli, and American novel Slaughterhouse-Five of Kurt Vonnegut, which are significant novels representing the intersection of personal choices and national power play, when a nation is completely shaken by war and societal change. In a comparative perspective, the study explicates how the two authors express the psychological and existential implications of violence, and it shows how political power abuses and limits the subjects. Vonnegut’s book, with its post-modern style and black humor, reflects the senselessness of war and the collapse of time for its hero, Billy Pilgrim. By contrast, Livaneli’s sensitive depiction of life on a remote island becomes a metaphor for wider social dislocations, portraying the battles for identity and permanence in a post-conflict world. Through the examination of representations of trauma, memory and resilience in both texts, this study seeks to uncover the ubiquitous influence of biopolitical violence on humanity in general thus further enabling a critical understanding of how literature mirrors and deconstructs the repressive tactics of state authority in a moment of crisis.